P47 Country of birth of mother and rates of preterm births and low birth weight in England and Wales of babies of African and Caribbean ethnicity. (16th November 2010) - Datta-Nemdharry, P; Macfarlane, A; Dattani, N
Abstract : Introduction: Preterm birth and low birth weight are associated with high rates of perinatal and neonatal morbidity and mortality. Some studies have shown associations between ethnic origin or country of birth and risk of preterm birth, But there are few analyses in which outcomes of birth, within a specific country, are classified by both mother's country of birth and ethnicity. Setting: Live singleton births in England and Wales of babies whose ethnicity was recorded as being Black African or Black Caribbean in 2005 and 2006. Aim: To compare rates of preterm birth and low birth weight in this group of babies born to mothers born in African and Caribbean countries or England and Wales. Method: In England and Wales birth weight and mother's country of birth are recorded at birth registration whereas ethnic group of baby and gestational age are recorded in the data set generated when the NHS number, a national unique patient identifier, is issued. Linking these two data sets has made it possible to assess the association between mother's country of birth, baby's ethnicity and birth outcomes. Data from the linked data set were used for the analysis. Countries were grouped according to UN geographical regions. Results: Mothers of babies of African ethnicity, born in Eastern or Northern Africa had significantly lower odds than those born in England and Wales of having a preterm baby. This remained significant after adjusting for mother's age at birth and sex of baby. In terms of low birth weight, after adjusting for gender, mother's age at birth and gestational age, mothers of babies of African ethnicity born in Middle and Western Africa had significantly lower odds of having a low birth weight baby compared with those born in England and Wales. Similarly, after adjusting for the available confounders, mothers of babies of Caribbean ethnicity, born in the Caribbean countries had lower odds of having a low birth weight baby compared with mothers born in England and Wales. Conclusion: Generally, preterm birth and low birth weight rates of babies of African or Caribbean migrant women born in England and Wales seems to be higher than those who migrated to England and Wales having themselves been born in African or Caribbean countries. Further research is needed about the possible causes of this difference in birth outcomes.